O contexto de trabalho e o adoecimento dos bancários do Estado do Ceará - Fontenelle, Marselle Fernandes (2021)
This thesis had as general objective to understand illness prevalence among workers in the banking sector in the state of Ceará, Brazil, due to their labour context. Specifically, (i) workers' perceptions about their workplace environment were verified; (ii) the prevalence of common mental disorders and RSI/WMSD among the participants was determined; (iii) the relationship between workplace environment and the prevalence of common mental disorders and RSI/WMSD, considering the sociodemographic aspects of the participants was investigated; and (iv) the illness of bank employees, considering the work environment and workers' perceptions was understood. Qualitative and quantitative data from these bank employees were collected through 8 semi-structured personal interviews and 912 validated questionnaires. Data was then analyzed through a cross-section regression model applied successively to three different dependent variables. The thesis consists of a theoretical contextualization chapter followed by 4 empirically oriented papers. The first theoretical chapter indicates that continued restructuring process have deeply changed the activity and labour context in these banking institutions, therefore resulting in intense process of job insecurity that impacts the health of workeforce in the banking sector. It was also verified – in three independent but with deeply interconnected empirical papers – the prevalence of: (1) Mental and Behavioral Disorders, (2) Depression and Anxiety and (3) Repetitive Strain Injuries/Work Related Musculoskeletal Disorders in the research participants. The main findings present in our papers indicate that these three pathologies are related, in a statistically significant way, with the organization of activities, socio-professional relationships and the working conditions in which labour is carried out by bank employees. Other relevant variables were evidenced throughout these studies, such as the relationship between the prevalence of these pathologies and the variables gender and professional position held by the individual in the bank, which points to promising lines of future research. The results of the interviews shows a process of continuous precarization of labour conditions in public and private owned banks, revealing the configuration of a work environment characterized by the intensification of the work pace, increased control and supervision of tasks and by amplifying pressure and demand for results. Unexpectedly, it is also noticed the presence of more collaborative socio-professional relationships and worsening of working conditions in public banks when compared to private banks. Respondents reported, in general, symptoms suggestive of RSI/WMSD and of psychological distress and the results obtained indicate that characteristics of labour environmnet are strongly associated with bank workforce illnesses, being predictors of several pathologies.